PENGUKURAN BIOMASSA DAN KARBON HUTAN TANAMAN JATI (Tectona grandis, L.f) DI KPH RANDUBLATUNG, PERUM PERHUTANI UNIT I JAWA TENGAH - , Haryo Pambudi, Dr. Ir. Ris Hadi Purwanto, M.Agr.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Indonesia is one of the main producers of teak (Tectona grandis, L.f) plantations in the world. Teak plantations are a long-term sink for carbon and play an important role in CO2 absorption. However, so far the equations for teak plantations have not been developed in total biomass and carbon (above+belowground). Total biomass and carbon measurements can be used (1) to develop allometric equations, Biomass Expansion Factor (BEF) and Carbon Expansion Factor (CEF), (2) to estimate the total biomass, total carbon and CO2 sequestrattion of teak plantations. The data were collected in KPH Randublatung, Perum Perhutani Unit I, Central Java, Indonesia. The number of tree sample in this research was 18 with 6 age class (KU). Destructive sampling method for sample tress with diameter at breast height (dbh) was used as predictor for total of biomass and carbon. Allometric equation relationship between dbh and total biomass as well as carbon was constructed and used to measure the total biomass and carbon storage in 10 age classes (KU I â KU X). Allometric equation relationship between dbh and total biomass was Bt = 0.133dbh 2.394 (R 2 0.974) while relationship dbh and total carbon was Kt = 0.088dbh 2.39 (R 2 0.977). Biomass Expansion Factor (BEF) that can be used to converse stem volume to total biomass content for ages 6